Development and validation of the Lebanese Social Media Dependency Scale (LSMDS): A cross-sectional study among university students - Samar Younes; Zeinab Abbas; Chadia Haddad; Daniele Saade; Nisreen Mourad; Hala Sacre; Amal Al-Hajje; Pascale Salameh (PLoS ONE, 2026)
Background Social media use has become pervasive among university students worldwide, with growing evidence linking excessive use to negative psychological and academic outcomes. While various scales exist to assess problematic social media use, most have been validated in Western populations, limiting their cultural applicability. This study aimed to develop and validate a culturally appropriate Lebanese Social Media Dependency Scale (LSMDS) for use among university students in Lebanon. Methods A cross-sectional study was conducted from March to April 2025 among 511 university students across Lebanon. The LSMDS was developed by selecting and refining items from three existing scales: the Smartphone Addiction Inventory (SPAI), Online Fear of Missing Out Inventory (ON-FoMO), and Social Media Disorder Scale (SMD). Exploratory factor analysis with oblimin rotation was performed to determine the factor structure. Construct and convergent validity were assessed, along with reliability testing using Cronbach’s alpha coefficients. Results The final LSMDS comprised 27 items organized into three factors explaining 52.91% of total variance: Problematic Smartphone Use (11 items), Social Media Validation Seeking (8 items), and Social Media Withdrawal Symptoms (8 items). The scale demonstrated excellent internal consistency (Cronbach’s α = 0.931) with strong reliability for individual factors (α = 0.847–0.913). Convergent validity was supported by significant correlations with SPAI (r = 0.863) and ON-FoMO (r = 0.888), and moderate correlation with SMD (r = 0.621). Single participants showed significantly higher LSMDS scores compared to married participants (47.50 vs 39.33, p = 0.037). Multivariable analysis revealed that a higher score on the attitudes toward artificial intelligence (Beta = 0.212) was significantly associated with a higher social media dependency. Conclusion The LSMDS represents a psychometrically sound, culturally relevant instrument for assessing social media dependency among Lebanese university students. Its three-factor structure captures distinct dimensions of social media dependency, providing researchers and practitioners with a valuable tool to identify and understand social media dependency patterns in the Lebanese context.